PENYULUHAN STRATEGI MENINGKATKAN PENDAPATAN ANGGOTA PADA KOPERASI PONDOK PESANTREN AL-MUTMAINAH - Syukri, Muhammad; Faezal, Faezal; Utami, Luh; Adhwa, Baiq Farhatul; Anwar, Muazin (LPPM Institut Pendidikan Nusantara Global, 2023)
Businesses run by cooperative members often lose competition and even fail due to poor financial management and the inability of members to adapt to the digital/online era and not being able to read existing business opportunities. On that basis, for the sake of business continuity of members, it is necessary to provide guidance and cooperative contact in business development as well as providing financial and administrative advice. The PKM (Community Service) team conducted PKM at the Al-Mutmainnah Islamic Boarding School Cooperative, Dasan Baru Village, Kediri District, West Lombok Regency to provide information on business development, financial management, and strategies to expand business fields and ultimately be able to increase the income of cooperative members. The benefits of PKM activities received by cooperative administrators and members are education and skills to expand business fields that can be applied so that member income increases. PKM implementation is in the form of material and practice aimed at cooperatives and monitoring. The management and members of the Al-Mutmainnah Islamic Boarding School Cooperative, which currently totals 45 people, are the targets of PKM activities. This activity uses material delivery methods, discussion forums, and business development strategies. Knowledge and skills are aspects that will be assessed in this PKM activity.